Objective Assessment of Activity, Energy Expenditure, and Functional Limitations in Older Men: The Osteoporotic Fractures in Men Study - Cawthon, Peggy M. (Oxford University Press, 2013)
BACKGROUND. The relationship between objectively assessed activity, energy expenditure, and the development of functional limitations is unknown. METHODS. Energy expenditure and activity levels were measured objectively using the multisensor SenseWear Pro Armband worn for greater than or equal to 5 days in 1,983 MrOS men (aged ≥78.3 years) free of functional limitations. Validated algorithms calculated energy expenditure; standard cut points defined moderate or greater activity (≥3.0 METS); and sedentary behavior (time awake ≤ 1.5 METS). Self-reported functional limitation was determined at the activity assessment and 2.0 years later as inability to perform instrumental activities of daily living (managing money, managing medications, shopping, housework, and meal preparation) and activities of daily living (climb stairs, walk two to three blocks, transfer, or bathe). RESULTS. Each standard deviation decrease in total energy expenditure (420.6 kcal/day) increased the likelihood of inability to perform an instrumental activity of daily living (multivariate odds ratio [mOR]: 1.61, 95% CI: 1.30–2.00) or activity of daily living (mOR: 1.35, 95% CI: 1.12–1.63). Each standard deviation decrease in moderate or greater activity (61.1 minutes/day) increased the likelihood of inability to perform an instrumental activity of daily living (mOR: 1.47, 95% CI: 1.22–1.78) or activity of daily living (mOR: 1.36, 95% CI: 1.14–1.61). Each standard deviation increase in minutes of sedentary behavior (105.2 minutes/day) increased the likelihood of inability to perform an instrumental activity of daily living (mOR: 1.20, 95% CI: 1.03–1.40) or activity of daily living (mOR: 1.17, 95% CI: 1.01–1.35). CONCLUSION. Older men with lower total energy expenditure, lower moderate activity, or greater sedentary time were more likely to develop a functional limitation.